Internet and broadband adoption in indigenous communities: An analysis of rural Alaska - Heather E. Hudson (International Telecommunications Society (ITS), 2012)
Alaska is the largest state in the U.S., but with the nation's lowest population density of only 1.2 persons per square mile. About 15 percent of the population are Alaska Natives. Approximately two-thirds of this indigenous population live in more than 200 villages, most of which are remote settlements without road access. A current broadband infrastructure project in rural southwest Alaska provides an opportunity to gather reliable data on rural broadband adoption and use, and perceived barriers to adoption among Alaska Natives. This paper presents an analytical framework for broadband adoption that takes into consideration the geographical and cultural environments in indigenous communities of rural Alaska. It then reports on results of an evaluation of Internet use and potential adoption and impacts of broadband in southwest Alaska. The first phase of the evaluation included a telephone survey of approximately 400 households of the region to gain information on current ownership of ICTs and Internet use. Interviews were also conducted with key informants from Native corporations and tribal organizations, economic development organizations, local businesses, and major sources of income such as fisheries, social services, and tourism to provide insights on potential benefits of broadband for rural development.
Keywords: 330